Supplementing transcranial direct current stimulation to local infiltration series for refractory neuropathic craniocephalic pain: A randomized controlled pilot trial - Wandrey, Jan D.; Kastelik, Joanna; Fritzsche, Thomas; Denke, Claudia; Schäfer, Michael; Tafelski, Sascha (Frontiers in Neurology, 2023)
Background Some patients with neuralgia of cranial nerves with otherwise therapy-refractory pain respond to invasive therapy with local anesthetics. Unfortunately, pain regularly relapses despite multimodal pain management. Transcranial direct current stimulation (tDCS) may prolong pain response due to neuro-modulatory effects. Methods This controlled clinical pilot trial randomized patients to receive anodal, cathodal or sham-tDCS stimulation prior to local anesthetic infiltration. Pain attenuation, quality-of-life and side effects were assessed and compared with historic controls to estimate effects of tDCS stimulation setting. Results Altogether, 17 patients were randomized into three groups with different stimulation protocols. Relative reduction of pain intensity in per protocol treated patients were median 73%, 50% and 69% in anodal, cathodal and sham group, respectively (p = 0.726). Compared with a historic control group, a lower rate of responders with 50% reduction of pain intensity indicates probable placebo effects (OR 3.41 stimulation vs. non-stimulation setting, NNT 3.63). 76.9% (n = 10) of tDCS patients reported mild side-effects. Of all initially included 17 patients, 23.5% (n = 4) withdrew their study participation with highest proportion in the cathodal group (n = 3). A sample size calculation for a confirmatory trial revealed 120 patients using conservative estimations. Discussion This pilot trial does not support series of anodal tDCS as neuro-modulatory treatment to enhance pain alleviation of local anesthetic infiltration series. Notably, results may indicate placebo effects of tDCS settings. Feasibility of studies in this population was limited due to relevant drop-out rates. Anodal tDCS warrants further confirmation as neuro-modulatory pain treatment option.